2011
DOI: 10.1124/mol.110.070243
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of Two New Positive Allosteric Modulators of GluA2 Desensitization and Deactivation

Abstract: At the dimer interface of the extracellular ligand-binding domain of ␣-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) receptors a hydrophilic pocket is formed that is known to interact with two classes of positive allosteric modulators, represented by cyclothiazide and the ampakine 2H,3H,6aH-pyrrolidino(2,1-3Ј,2Ј)1,3-oxazino(6Ј,5Ј-5,4)benzo(e)1,4-dioxan-10-one (CX614). Here, we present structural and functional data on two new positive allosteric modulators of AMPA receptors, phenyl-1,4-bisalkylsulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 68 publications
3
57
0
Order By: Relevance
“…To address whether the addition of the fluorophore impacted our results, we compared the kinetics of the fusion protein with that of untagged recombinant receptors and concluded that the addition of the C-terminal fluorophore to GluA2 did not alter receptor kinetics. Specifically, the time constants for deactivation and desensitization of the WT receptor, 0.79 and 1.64 ms, respectively, are very consistent with time constants reported in other published reports (our own and others) using untagged receptors with deactivation kinetics in those reports ranging from 0.71 to 0.92 ms and desensitization kinetics ranging from 1.18 to 1.87 ms (3,11,41,42). Thus, although there is a possibility that the unique functional properties of R628E may have been influenced by the C-terminal reporter protein, this is a less likely interpretation of our results as both the WT and mutant proteins contained the enhanced GFP sequences.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…To address whether the addition of the fluorophore impacted our results, we compared the kinetics of the fusion protein with that of untagged recombinant receptors and concluded that the addition of the C-terminal fluorophore to GluA2 did not alter receptor kinetics. Specifically, the time constants for deactivation and desensitization of the WT receptor, 0.79 and 1.64 ms, respectively, are very consistent with time constants reported in other published reports (our own and others) using untagged receptors with deactivation kinetics in those reports ranging from 0.71 to 0.92 ms and desensitization kinetics ranging from 1.18 to 1.87 ms (3,11,41,42). Thus, although there is a possibility that the unique functional properties of R628E may have been influenced by the C-terminal reporter protein, this is a less likely interpretation of our results as both the WT and mutant proteins contained the enhanced GFP sequences.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, wild type constructs were modified to include the R607Q mutation to enhance currents for patch clamp electrophysiology as described previously (11). Thus, the term wild type ("WT") used in this study refers to GluA2 R607Q.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Site II Side-chain Truncations Impart Sensitivity to AMPA Receptor Positive Modulators-In AMPA receptors, the equivalent location of site II residues defines the binding pocket for small allosteric modulators, which potentiate currents by slowing macroscopic deactivation (11,30,31,(43)(44)(45)(46). The "floor" of this binding pocket is lined by serine residues absent in NMDA receptors (Fig.…”
Section: Glutamate Dissociates Slower From N1 Y/w -In Contrast To N1mentioning
confidence: 99%